Polariton Spectroscopy: Nanoimaging and Nanospectroscopy of Polaritons with Time Resolved s‐SNOM (Advanced Optical Materials 5/2020). Issue 5 (5th March 2020) - Yao, Ziheng; Xu, Suheng; Hu, Debo; Chen, Xinzhong; Dai, Qing; Liu, Mengkun
Abstract : Time‐resolved nanoimaging of polaritons using scanning near‐field optical microscopes is highlighted in a progress report by Ziheng Yao, Qing Dai, Mengkun Liu and co‐workers (article number 1901042 ). The measurement of ultrafast dynamics of polariton propagation with nanoscale resolution is only recently achievable with the advances in laser and near‐field techniques. The creation and probing of the tip‐ and edge‐induced plasmon‐polaritons and phonon‐polaritons in low‐dimensional systems are discussed in detail.